황금(Scutellaria baicalensis)에 안전한 토양 및 경엽처리 제초제 - 송종석(Jong-Seok Song); 임지수(Jisoo Lim); 장전걸(Chuanjie Zhang); 김도순(Do-Soon Kim) (Weed & turfgrass science, 2019)
본 연구는 황금에 안전한 토양 및 경엽처리 제초제를 선발하고자 수행하였다. 황금 생육기에 다양한 약제를 1/2배량, 기준량, 2배량으로 처리한 후 달관평가를 통하여 약해를 조사하였다. 토양처리 제초제를 처리한 후 30일에 조사한 결과 황금의 출아에 가장 영향이 적은 제초제는 pendimethalin이었으며, 출아 이후 처리에서 약해가 적은 제초제는 alachlor, napropamide, pendimethalin 이었다. 경엽처리용 제초제의 경우 황금의 5-6엽기 처리는 약해가 컸으며, 황금의 11-12엽기에 nicosulfuron과 thifensulfuron의 처리는 약해가 적어 황금의 경엽처리 제초제로 사용이 가능할 것으로 판단되었다. 따라서 선발된 pendimethalin을 포함한 토양처리제와 경엽처리제로서 nicosulfuron과 thifensulfuron을 황금재배시기를 고려하여 적절히 체계 처리한다면 황금재배에 적합한 잡초방제가 가능할 것으로 판단되며, 이를 위해서는 추가적으로 포트실험 단계에서 적정 농도를 확립하고 보다 체계적인 포장에서의 현장평가가 필요할 것으로 사료된다. Lack of herbicides for Scutellaria baicalensis, one of the most important medicinal herbs in traditional Korean medicine, has led to a poor weed control in S. baicalensis cultivation. A greenhouse experiment was conducted to select safe pre-emergence (PRE) and post-emergence (POST) herbicides for S. baicalensis. Of the 6 PRE herbicides tested, pendimethalin only showed an acceptable damage on pre-emergent S. baicalensis even at double the rate of its recommended dose, and alachlor, napropamide, and pendimethalin showed very low damage on post-emergent S. baicalensis. Scutellaria baicalensis was significantly damaged by all the tested POST herbicides at its 5 to 6 leaf stage. Of them, acetolactate synthase inhibitors such as nicosulfuron and thifensulfuron showed relatively low damage, 6% and 15% at double the rates of their recommended doses, respectively, when applied at the 11 to 12 leaf stage of S. baicalensis. Therefore, these results demonstrate that pendimethalin as a PRE herbicide and thifensulfuron and nicosulfuron as a POST herbicide can be sequentially used for weed control in S. baicalensis cultivation. KCI Citation Count: 0